2004
DOI: 10.1890/01-4101
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Population Dynamics of a Dominant Rain Forest Canopy Tree

Abstract: Intraspecific, negative density dependence may contribute to the maintenance of diversity by limiting the dominance of common species. Shorea quadrinervis Slooten (Dipterocarpaceae) is one of the dominant canopy trees in a species‐rich tropical rain forest in Southeast Asia. We test whether juvenile density and performance and overall population growth rate of S. quadrinervis decline with increasing local abundance of conspecific adult trees. We mapped the 357 S. quadrinervis adults (≥15 cm dbh) in 75 ha at Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 36 publications
3
62
0
1
Order By: Relevance
“…It provides a mechanism for the recruitment of rare species, and has been interpreted more generally as an effect of conspecific density, not just distance from parent trees (Hammond and Brown, 1998;Wright, 2002;Terborgh, 2012). Evidence indicates that such negative densitydependent recruitment is widespread during the seed-to-seedling transition stage (Blundell and Peart, 2004;Wright et al, 2005;Kobe and Vriesendorp, 2011). In contrast to the Janzen-Connell model, the predator satiation hypothesis predicts that seed attack is reduced in high-seed years or in areas with high seed densities, leading to positive density-dependent recruitment of common species (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a mechanism for the recruitment of rare species, and has been interpreted more generally as an effect of conspecific density, not just distance from parent trees (Hammond and Brown, 1998;Wright, 2002;Terborgh, 2012). Evidence indicates that such negative densitydependent recruitment is widespread during the seed-to-seedling transition stage (Blundell and Peart, 2004;Wright et al, 2005;Kobe and Vriesendorp, 2011). In contrast to the Janzen-Connell model, the predator satiation hypothesis predicts that seed attack is reduced in high-seed years or in areas with high seed densities, leading to positive density-dependent recruitment of common species (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the tests mentioned were almost all from one site (there are occasional scattered single-species examples from elsewhere, e.g., for seedlings ,1 cm dbh only; Blundell and Peart [2004]), it is doubtful whether it can be generally concluded for tropical forests that NDD is operating among seedlings only, and not sometimes (or even frequently) just as strongly among the small-tree size class. At other sites, the situation might be reversed, or a mixture of NDD mechanisms operate.…”
Section: Introductionmentioning
confidence: 99%
“…The Ricker, BevertonHolt, and power functions include only negative effects of density (but see Myers et al 1995 for a modified version of the Beverton-Holt function that incorporates positive density dependence). In contrast, Blundell and Peart (2004) found that early seedling recruitment in a tropical tree population was positively density dependent, probably because of predator satiation. In such cases, we will need to develop models that incorporate both positive and negative effects of density, whose relative importance changes as a function of seed density.…”
Section: Applying and Extending The Frameworkmentioning
confidence: 83%